Cognitive Side Effects of Antiepileptic Drugs - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Available studies of the cognitive side effects of traditional and newer antiepileptic drugs (AEDs) are reviewed by researchers at Georgetown University Medical Center, Washington, DC.